The modulation of crossmodal integration by unimodal perceptual grouping: a visuotactile apparent motion study. - Lyons, G; Sanabria, D; Vatakis, A; Spence, C (2006)
We adapted the crossmodal dynamic capture task to investigate the modulation of visuotactile crossmodal integration by unimodal visual perceptual grouping. The influence of finger posture on this interaction was also explored. Participants were required to judge the direction of a tactile apparent motion stream (moving either to the left or to the right) presented to their crossed or uncrossed index fingers. The participants were instructed to ignore a distracting visual apparent motion stream, comprised of either 2 or 6 lights presented concurrently with the tactile stimuli. More crossmodal dynamic capture of the direction of the tactile apparent motion stream by the visual apparent motion stream was observed in the 2-lights condition than in the 6-lights condition. This interaction was not modulated by finger posture. These results suggest that visual intramodal perceptual grouping constrains the crossmodal binding of visual and tactile apparent motion information, irrespective of finger posture.